2020
DOI: 10.1101/2020.09.16.20196071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 and human milk: SARS-CoV-2, antibodies, and neutralizing capacity

Abstract: Background: It is not known whether SARS-CoV-2 can be transmitted from mother to infant during breastfeeding, and if so whether the benefits of breastfeeding outweigh this risk. This study was designed to evaluate 1) if SARS-CoV-2 RNA can be detected in milk and on the breast of infected women, 2) concentrations of milk-borne anti-SARS-CoV-2 antibodies, and 3) the capacity of milk to neutralize SARS-CoV-2 infectivity. Methods: We collected 37 milk samples and 70 breast swabs (before and after breast washing) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
89
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 38 publications
12
89
1
5
Order By: Relevance
“…Our results provide a snapshot of the dynamic immune response in colostrum following SARS-CoV-2 infection, confirming recent findings on the presence of SARS-CoV-2-specific antibodies in milk from infected women4,5 , and describing for the first time, the associated cytokine profile. Colostrum samples archived before the pandemic together with analysis of bilateral samples provide important controls for this study, and the similarities between resultsfrom the spot card and the liquid colostrum demonstrate the value of the spot card collection method.…”
supporting
confidence: 89%
“…Our results provide a snapshot of the dynamic immune response in colostrum following SARS-CoV-2 infection, confirming recent findings on the presence of SARS-CoV-2-specific antibodies in milk from infected women4,5 , and describing for the first time, the associated cytokine profile. Colostrum samples archived before the pandemic together with analysis of bilateral samples provide important controls for this study, and the similarities between resultsfrom the spot card and the liquid colostrum demonstrate the value of the spot card collection method.…”
supporting
confidence: 89%
“…A small number of reports have shown that antibodies against SARS-CoV-2 can be detected in the breastmilk of breastfeeding women who have recovered from documented SARS-CoV-2 infection [ 4-6 ]. The largest of these reports investigated 37 breastfeeding women with recent documented SARS-CoV-2 infection finding that all (100%) had detectable SARS-CoV-2 IgA and IgG [ 7 ], while another investigating 15 breastfeeding women found that 12/15 (80%) had detectable IgA and IgG reactive to the SARS-COV-2 RBD-antigen [ 4 ]. Two other reports describe two individual patients: a pregnant woman with active SARS-CoV-2 infection who delivered an infant who had detectable IgA and IgG in her breastmilk [ 5 ], and a breastfeeding woman found to have SARS-CoV-2 IgG and IgM in her breastmilk (IgA was not tested) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the already well-known and documented benefits of breastfeeding (3), recent research has shown specific benefits relevant to the COVID-19 situation. For example, antibodies to SARS-CoV-2 have recently been isolated in human milk (34)(35)(36) and have shown strong SARS-CoV-2 neutralizing capabilities (18,37). Whilst these data show a robust immunological response by human milk against the virus they also suggest that human milk provides an active form of protection against the virus, a form of protection that cannot be provided to the infant via artificial formula, thus further supporting the need for the protection and promotion of breastfeeding.…”
Section: Discussionmentioning
confidence: 95%